Pharmacy students’ initial career choices versus subsequent career paths: a cross-sectional study - Roy Kanbar; Aline H. Saad; Imad F. Btaiche (BMC Medical Education)
Abstract Background The pharmacy profession offers diverse career paths. Yet, pharmacy students may not be familiar with these various paths and may struggle to choose one that is best suited to their interests, goals, and values. Limited literature has reported on pharmacy students’ career interests. However, no studies have evaluated pharmacy graduates’ eventual career paths as compared to their initial choices when they were students. Therefore, the primary objective of this study was to compare pharmacy students’ initial career choices to their subsequent career paths. Methods This was a descriptive cross-sectional study that analyzed data on pharmacy students’ initial career choices when they were enrolled in a career opportunities course and their subsequent career paths following graduation. Data on the initial career choices of students were retrospectively collected from the records of a career opportunities elective course between the academic years 2012 and 2019. Based on previous employment surveys, data on the subsequent graduates’ career paths and graduate and postgraduate education were retrieved from the school records. Subsequent graduates’ career paths were then compared to their individual students’ initial career choices. The paths of graduates with a Doctor of Pharmacy (PharmD) versus Bachelor of Science in Pharmacy (BS Pharm) only holders were analyzed. Results The overall subsequent career paths of graduates matched the initial students’ career choices in 30.8% of cases. While the top initial students’ career choices were community pharmacy (36.1%), clinical pharmacy (31.4%), and pharmaceutical industry (12.9%), the top subsequent graduates’ career paths were however the pharmaceutical industry (30.7%), community pharmacy (17.9%), and clinical pharmacy (7.9%). Work in the pharmaceutical industry and community pharmacy and the pursuit of masters and/or PhD were mostly followed by BS Pharm graduates, whereas PharmD holders predominantly pursued clinical pharmacy. Conclusions Pharmacy graduates’ career paths infrequently matched their initial career choices as students. Pharmacy curricula should prepare students for diverse career paths.